Community gathered on an agricultural field - Mumbai Archive Project Team (Jio Institute, 2024)
The events recreate a typical day in a farmer’s life. The community gathers on an agricultural field for a special service organized by the local parish of Our Lady of Bethlehem Church, located in Dongri-Tarodi village.